Changing cropping pattern in U.P. Bundelkhand region - Swati Yadav (National Geographical Journal of India, 2021)
Agriculture is a dominant economic activity in India. About 70% of its population is directly or indirectly related and dependent on agriculture so the availability of land for cultivation is important for those people who are engaged in agriculture. Cropping pattern is also an important aspect to know the agricultural scenario of any area. The pattern of cropping is very much affected by population growth and other physical and economic factors. In this paper, an attempt has been made to analyze the changing cropping pattern in Bundelkhand Region in the last two decades from 1994-95 to 2014-15.The major crops that occupy the agricultural land of the region are Cereals (40.52%), Pulses (41.06%), Oilseeds (15.46%), Cash crops (1.31%), Fodder (0.35%) and Other crops (1.29%). In this time of 20 years (1994-95 to 2014-15), a trend of positive change is found in all groups except fodder and other crops.